Examining the Determinants of Customer Satisfaction in Medicine and Health Device Distributors - Adi, I Nyoman Rasmen; Saputri, Luh Gede Elvina Adi (Journal of Social Work and Science Education, 2024)
Through an in-depth understanding of these factors, drug and medical device distributors can develop strategies to increase their customer satisfaction, strengthen business relationships, and create added value in a competitive market. This research aims to analyze the role of distribution channel activities and promotional activities in increasing satisfaction and creating customer loyalty in drug distribution companies in Denpasar. This research uses quantitative methods with a Structural Equation Modeling approach using Smart Partial Least Square (SEM-PLS) version 4. The research results found that (1) increased customer satisfaction can be created through a good distribution channel system and promotional activities that are carried out appropriately; (2) High customer loyalty can be created through a good distribution system, good promotional activities, and high customer satisfaction; (3) customer satisfaction is proven to act as a mediating construct between the relationship between distribution and loyalty and promotion and loyalty. This research provides recommendations for drug distribution companies in increasing customer loyalty and satisfaction through determining appropriate distribution channels and implementing good promotions.